The relationship between fertility and female participation in the labour force in OECD countries 2000-2020: It is (again) negative - Miloš Milovanović (Central European Economic Journal (CEEJ), 2023)
The cross-sectional association between female labour force participation rates and fertility in developed countries shifted from negative to positive during the 1980s. Ever since then, researchers have applied different statistical approaches; therefore, the present study re-evaluates the results by applying a distinct strategy to the data from 2000 to 2020 for 32 countries belonging to the Organization for Economic Co-operation and Development (OECD). Specifically, the data analysis discussed here implemented the so-called "unified" model, thereby extending the analysis beyond the limitations of the fixed effects (FE) method; namely, by decomposing coefficients within (time-series) and between (cross-sectional) countries' effects, the study increased the explanatory power of our statistical model on the relation between fertility level and female labour force participation rate. Eventually, the selected statistical approach has shown the potential to offer a better interpretation of results in comparison to previous studies. Finally, this study confirmed the persistence of a negative trend in a time-series association between labour force participation and fertility.
Keywords: J13; J21; C33; C18; 330; Female labour force participation; fertility rate; global financial crisis; total fertility rates